Masculine Violence and Homoeroticism: from Mauricio Wacquez to Daniel O’Hara (Anclajes, 2018)
Analysis of a pioneering novel in the representation of male homoeroticism, Ella o el sueño de nadie (1983), by Chilean author Mauricio Wacquez, in contraposition to the short story “Rapsodia metropolitan” (2007), by Barcelonese writer Daniel O’Hara, both published in “La sonrisa vertical” [“Vertical Smile”], one of the most important Hispanic erotic collections of the last quarter of the 20th century. These fictions, focused on the representation of a violent heterodox masculinity -and published almost a quarter of a century apart- and transgressive because of their visibilization of homoerotic practices, are still far from any type of vindication of a minority sexuality.
Keywords: “La sonrisa vertical”; Spanish Literature; Sexual Minorities; 21st Century; Spain